2011
DOI: 10.1164/rccm.201007-1173oc
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer T Cell–derived IL-17 Mediates Lung Ischemia–Reperfusion Injury

Abstract: Rationale: We recently implicated a role for CD4 1 T cells and demonstrated elevated IL-17A expression in lung ischemia-reperfusion (IR) injury. However, identification of the specific subset of CD4 1 T cells and their mechanistic role in IR injury remains unknown. Objectives: We tested the hypothesis that invariant natural killer T (iNKT) cells mediate lung IR injury via IL-17A signaling. Methods: Mice underwent lung IR via left hilar ligation. Pulmonary function was measured using an isolated lung system. Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 45 publications
5
134
0
1
Order By: Relevance
“…Previous reports suggested that CD4 + T cells, NKT cells, and gd T cells produce IL-17A (26,36,37). Specifically, CD8 + cells produce IL-17A in patients with chronic obstructive pulmonary disease (38).…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports suggested that CD4 + T cells, NKT cells, and gd T cells produce IL-17A (26,36,37). Specifically, CD8 + cells produce IL-17A in patients with chronic obstructive pulmonary disease (38).…”
Section: Discussionmentioning
confidence: 98%
“…NKT cells initiate inflammation following IRI in liver, lung, and/or kidney (4,5). By studying NKT cell-deficient mice and by blocking DC-NKT cell interaction, we demonstrated that CD1d-restricted NKT cells are necessary for kidney IRI.…”
Section: Introductionmentioning
confidence: 88%
“…We and others have shown that NKT cells contribute to organ IRI (5,6,48,49). Interrupting the DC-NKT cell interaction, depleting CD1d-restricted NKT cells, or using NKT cell-deficient mice (CD1d KO) protected kidney from IRI (6).…”
Section: Figurementioning
confidence: 99%
“…neutrophil/mononuclear phagocyte activation and infiltration) (30), and proinflammatory cytokines and chemokines (7,8,15,20,24), all exemplifying multiple complex inflammatory pathways involved in PGD.…”
Section: Introductionmentioning
confidence: 99%